Analysis of consumer satisfaction influenced by service quality, servicescape, and price perceptions - Leonardo Indra Vitaharsa (Institute of Computer Science (IOCS), 2023)
The primary objective of this article is to examine the level of customer satisfaction (Y) within a restaurant, exploring how it is influenced by three key factors: service quality (X1), servicescape (X2), and price perception (X3). The Likert scale is used in preparing measurement instruments. We used a random sample of 30 respondents to test the validity and reliability. We used 90 respondents for statistical analysis of multiple linear regression with the application of SPSS-26 statistics to prove the hypothesis of simultaneous effect and partial effect. We use this sample size. Roscoe's method is 20 times the number of variables with minimal assumptions. The results of this study reveal the simultaneous influence of the three independent variables on the dependent variable. Service Quality partially influences the variable customer satisfaction, customer satisfaction is not affected by servicescape, and Price Perceptions affect customer satisfaction.